2017
DOI: 10.5114/aic.2017.70190
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and clinical outcome in patients with symptomatic carotid artery stenosis after carotid artery revascularization

Abstract: IntroductionAbout 30% of patients with carotid artery stenosis (CAS) develop dementia after a cerebral ischemic event (CIE), and 20–50% suffer from CIE recurrence during 6 months. Carotid artery revascularization (CAR) may prevent CIE recurrence, at the cost of new microembolic lesions (MES). The impact of CAR on cognitive function is debatable.AimTo assess functional and cognitive outcome, cerebral flow on transcranial Doppler (TCD) and brain magnetic resonance imaging (MRI) in patients with symptomatic CAS r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…This data were supported by the results of the observational study in a group of 42 patients with high-grade, asymptomatic carotid artery stenosis, in which cognitive impairment correlated linearly with mean flow velocity below a threshold of < 45 cm/s in the hemisphere fed by the stenosed internal carotid artery [30]. In line, carotid artery stenosis may be associated with mild cognitive impairment in either neurologically symptomatic and asymptomatic patients [26,33]. Puz et al, in group of 60 patients with ulcerated plaque causing internal carotid artery stenosis ≥ 70%, showed reduced cerebrovascular reactivity, indicating important role of TCCD examination [34].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This data were supported by the results of the observational study in a group of 42 patients with high-grade, asymptomatic carotid artery stenosis, in which cognitive impairment correlated linearly with mean flow velocity below a threshold of < 45 cm/s in the hemisphere fed by the stenosed internal carotid artery [30]. In line, carotid artery stenosis may be associated with mild cognitive impairment in either neurologically symptomatic and asymptomatic patients [26,33]. Puz et al, in group of 60 patients with ulcerated plaque causing internal carotid artery stenosis ≥ 70%, showed reduced cerebrovascular reactivity, indicating important role of TCCD examination [34].…”
Section: Discussionsupporting
confidence: 52%
“…This unexpectedly high values of the RI and the PI in patients with DAS, that obviously indicate failure of the physiological autoregulation mechanism in response to reduced CBF, can be partially explained by the negative impact of age and coexisting comorbidities, such as diabetes, hyperlipidemia and hypertension resulting in the increased stiffness in the macro-vasculature and small-vessel disease [26][27][28][29].…”
Section: Discussionmentioning
confidence: 98%
“…[17][18][19][20][21] However, Rafat et al found no association between the appearance of a high-signal-intensity area on DWI after surgery and higher brain hypofunction. 22) In this study, the KPOT II results significantly improved even in the DWI-positive group. However, deterioration was noted in one patient in this group, suggesting that the appearance of predominant-side cerebral infarction is involved in higher brain hypofunction.…”
Section: ) Appearance Of Positive Findings On Dwi and Higher Brain Fsupporting
confidence: 47%
“…The assessment of eligibility for interventional treatment in patients with symptomatic stenosis is based not only on the benefit in the secondary stroke prevention but also on data indicating the improvement of cerebral flow and perfusion and the functional outcome, as well as the potential positive impact on cognitive functions. 29 Treatment choice and the identification of patients at increased risk are much more difficult in asymptomatic individuals.…”
Section: Resultsmentioning
confidence: 99%